Efectiveness of Blended Learning Model in Indonesian Language Learning for PGSD Students at Universitas Terbuka - Angga Warda Prasakti; Yasir Riady; Nazurty (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The purpose of this study is to investigate the ways in which blended learning can enhance students' comprehension of Indonesian language learning in elementary school. The research is a study on Indonesian language learning using blended learning methods. Through the utilization of qualitative descriptive methods and the utilization of data triangulation techniques, researchers are able to improve the findings of the research and reduce any biases that may occur throughout the process of data collecting and analysis. Based on the findings of this study, it can be observed that the level of comprehension possessed by students enrolled in the Postgraduate Diploma in Education (PGSD) program at the Open University has significantly improved, as demonstrated by the exceptional learning values they possess. With the help of this research, it is intended that it will provide a more in-depth understanding of the advantages and difficulties associated with the implementation of blended learning, as well as make recommendations for the construction of a more effective educational system in the future. There is also the possibility that the consequences of the research findings can serve as the foundation for more research paths in this area. By way of illustration, a university may employ blended learning by integrating online lectures with traditional classroom instruction.